Integral Inequalities on Time Scales via the Theory of Isotonic Linear Functionals. (25th July 2011) - Anwar, Matloob; Bibi, Rabia; Bohner, Martin; Pečarić, Josip
Abstract : We apply the theory of isotonic linear functionals to derive a series of known inequalities, extensions of known inequalities, and new inequalities in the theory of dynamic equations on time scales.